Impact of Green Innovation on Firm Value: Evidence From Listed Companies in China’s Heavy Pollution Industries - Xie, Zhaodong; Wang, Jianzhi; Zhao, Guoqin (Frontiers in Energy Research, 2022)
The unspecified impact of green innovation on CFP has made some enterprises delay green innovation investment plans, and even abandon green innovation. Mitigating the economic concerns faced in the process of green innovation decision-making is of great significance to accelerate the process of enterprises’ green transformation. Using an unbalanced panel data of Chinese heavy pollution listed companies from 2008-2017, this paper investigates the impact of green innovation on firm value. We further test the likely channels through which green innovation can affect firm value, including the financial flexibility channel and analyst coverage channel. The study finds that: (1) increasing the proportion of green patent applications leads to the devaluation of firm value, but this devaluation effect only occurs in the short term; (2) both financial flexibility and analyst coverage partially mediate the impact of green innovation on firm value; (3) heterogeneity analysis indicates that enterprises can reduce the negative impact of green innovation on firm value by increasing the executive equity incentive and the management-employee pay gap. In addition, as economic policy uncertainty increases from low to high, the negative impact becomes smaller. Our research helps to broaden the cognitive boundaries of the economic impact of green innovation, and assists policymakers and researchers to better grasp the characteristics of green innovation behavior of enterprises in emerging economies. Finally, we provide useful enlightenments for policymakers and business managers to stimulate green innovation in enterprises.